A re-description of the fossil damselfly Eolestes syntheticus Cockerell, 1940 (Odonata: Zygoptera: Eolestidae n. fam.) with description of new taxa from the Eocene of North America - Greenwalt, Dale E.; Bechly, Günter (Zootaxa, 2014)
The enigmatic species Eolestes syntheticus Cockerell, 1940, from the Early Eocene of North America, previously attributed to the lestoid family Synlestidae, is re-examined in light of the discovery of new material from the Middle Eocene Kishenehn Formation in northwestern Montana. E. syntheticus and a new species, Eolestes ramosus sp. n., are attributed to a new family Eolestidae fam. n.. In addition, a new genus and species very closely related to Lestidae but assigned to family unknown, Lutetialestes uniformis sp. n., is described from the Kishenehn Formation.